Influence of crown-to-implant ratio, retention system, restorative material, and occlusal loading on stress concentrations in single short implants - Sotto-Maior, Bruno Salles; Senna, Plinio Mendes; Da Silva, Wander José; Rocha, Eduardo Passos [UNESP]; Del Bel Cury, Altair Antoninha (My University, 2012)
Purpose: The aim of this study was to assess the contributions of some prosthetic parameters such as crownto- implant (C/I) ratio, retention system, restorative material, and occlusal loading on stress concentrations within a single posterior crown supported by a short implant. Materials and Methods: Computer-aided design software was used to create 32 finite element models of an atrophic posterior partially edentulous mandible with a single external-hexagon implant (5 mm wide × 7 mm long) in the first molar region. Finite element analysis software with a convergence analysis of 5% to mesh refinement was used to evaluate the effects of C/I ratio (1:1; 1.5:1; 2:1, or 2.5:1), prosthetic retention system (cemented or screwed), and restorative material (metal-ceramic or all ceramic). The crowns were loaded with simulated normal or traumatic occlusal forces. The maximum principal stress (smax) for cortical and cancellous bone and von Mises stress (svM) for the implant and abutment screw were computed and analyzed. The percent contribution of each variable to the stress concentration was calculated from the sum of squares analysis. Results: Traumatic occlusion and a high C/I ratio increased stress concentrations. The C/I ratio was responsible for 11.45% of the total stress in the cortical bone, whereas occlusal loading contributed 70.92% to the total stress in the implant. The retention system contributed 0.91% of the total stress in the cortical bone. The restorative material was responsible for only 0.09% of the total stress in the cancellous bone. Conclusion: Occlusal loading was the most important stress concentration factor in the finite element model of a single posterior crown supported by a short implant. © 2012 by Quintessence Publishing Co Inc.
Keywords: Alveolar bone atrophy; Dental implant; Finite element analysis